2020
DOI: 10.1101/2020.01.27.921379
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Abnormal center of mass control during balance: a new biomarker of falls in people with Parkinson’s disease

Abstract: Although Parkinson disease (PD) causes profound balance impairments, we know very little about how PD impacts the sensorimotor networks we rely on for automatically maintaining balance control. In young healthy people and animals, muscles are activated in a precise temporal and spatial organization when the center of body mass (CoM) is unexpectedly moved.This organization is largely automatic and determined by feedback of CoM motion. Here, we show that PD alters the sensitivity of the sensorimotor feedback tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 94 publications
0
5
0
Order By: Relevance
“…Sensorimotor beta oscillatory activity is sustained throughout balance recovery with a time course resembling balance-correcting muscle activation. Our lab previously demonstrated that during reactive balance recovery the central nervous system directly scales the initial automatic motor response with body motion at a delay of 100 ms [ 4 , 5 , 60 , 65 ]. The similarity of the time course of the initial beta activity to that of the motor responses suggests the possibility that a common source of integrated sensory inputs [ 66 , 67 ] may drive both the initial automatic motor response (at ~100 ms delay) and the early phase of evoked cortical beta activity (at ~50 ms delay) during balance reactions.…”
Section: Discussionmentioning
confidence: 99%
“…Sensorimotor beta oscillatory activity is sustained throughout balance recovery with a time course resembling balance-correcting muscle activation. Our lab previously demonstrated that during reactive balance recovery the central nervous system directly scales the initial automatic motor response with body motion at a delay of 100 ms [ 4 , 5 , 60 , 65 ]. The similarity of the time course of the initial beta activity to that of the motor responses suggests the possibility that a common source of integrated sensory inputs [ 66 , 67 ] may drive both the initial automatic motor response (at ~100 ms delay) and the early phase of evoked cortical beta activity (at ~50 ms delay) during balance reactions.…”
Section: Discussionmentioning
confidence: 99%
“…Sensorimotor beta oscillatory activity is sustained throughout balance recovery with a time course resembling balance-correcting muscle activation. Our lab previously demonstrated that during reactive balance recovery the central nervous system directly scales the initial automatic motor response with body motion at a delay of 100 ms (McKay et al, 2020;Welch & Ting, 2008. The similarity of the time course of the initial beta activity to that of the motor responses suggests the possibility that a common source of integrated sensory inputs (He et al, 1991;Lockhart & Ting, 2007) may drive both the initial automatic motor response (at ~100 ms delay) and the early phase of evoked cortical beta activity (at ~50 ms delay) during balance reactions.…”
Section: Role Of Sensorimotor Cortical Processing In Standing Balancementioning
confidence: 99%
“…Three fixed COM feedback delay conditions were used to investigate the effect of delayed feedback: 𝑡 𝐷 = 100, 150, and 200 ms. These delay conditions were modeled to reflect the sensory feedback delay observed in the elderly population [46]. The magnitude of the sinusoidal perturbation applied to the platform was increased from 0 to 80 mm, where the 0 to 10 mm range was incremented by 2 mm and the 10 mm to 80 mm was incremented by 20 mm.…”
Section: Optimization and Simulation Setupmentioning
confidence: 99%
“…where 𝑝 indicates the position and 𝑝 indicates the velocity of the foot or wholebody COM; and 𝐾 𝐶𝑃 and 𝐾 𝐶𝑉 are the feedback control gains for position and velocity respectively, and 𝑡 𝐷 is the COM feedback delay. The range of delays used were adapted from the study by McKay et al [46], which looked at sensory feedback and balance in individuals with Parkinson's disease compared to elderly individuals without Parkinson's disease; in this study they provided a sensorimotor feedback model that successfully reproduced muscle activations as seen in experimental trials with healthy, aging, and Parkinson's disease subject groups. Equation (3) differs from the equation used in McKay et al's study by using a comparison of whole body COM position to foot COM position.…”
Section: Gluteus Maximus and Hamstrings Iliopsoas Hamstrings And Bice...mentioning
confidence: 99%
See 1 more Smart Citation